Guía: Realidad Aumentada como Estrategia Didáctica para la Docencia de Ciencias Naturales - Remache Molina, Deysi Soraya (2025)
The present research aimed to evaluate the effectiveness of augmented reality as a didactic strategy in the teaching of Natural Sciences. Modern teaching should be active and dynamic, capturing students’ attention and moving away from traditional practices toward a more meaningful educational experience. To support this goal, a didactic guide was developed to facilitate the use of augmented reality applications focused on Natural Sciences topics. This guide was combined with targeted didactic strategies to enhance pedagogical practices. The research employed a mixed-methods approach. Initially, a qualitative approach was applied, as the study was conducted in a humanistic and social context, specifically within the field of education. A quantitative approach was also incorporated to enable mathematical and statistical analysis of the collected data. The research followed a non-experimental design, as no variables were manipulated. It was exploratory, descriptive, basic, and propositive in nature. Regarding its scope, the study was fieldbased and bibliographic, conducted within a cross-sectional timeframe. Data collection was carried out using a survey technique, with a Likertscale questionnaire administered to twelve Natural Sciences teachers at the middle sublevel of the “San Felipe Neri” Educational Unit. The collected data were objectively interpreted by the authors. The study concluded that augmented reality, when used as a didactic strategy, enhances teaching practices in the Natural Sciences. Its implementation fosters the development of competencies, skills, and digital abilities among teachers, enabling them to perform their pedagogical work in an innovative and engaging manner.